First report of Bipolaris cactivora causing brown leaf spot in rice in Malaysia - M. Z., Nur Ain Izzati; M. Z. A., Madihah; K., Nor Azizah; A., Najihah; M., Muskhazli (American Phytopathological Society Publications, 2019)
In March 2013 to February 2017, brown spot symptoms on the leaves of rice plants were observed during a survey conducted in 23 granary fields throughout Peninsular Malaysia in Kedah, Penang, Perak, and Selangor states. In Malaysia, leaf spot symptoms can be seen on the rice seedling up to mature rice plant. Symptoms of the leaf spot include brown necrotic spots, which are irregular and measure between 2 and 10 mm wide. Small pieces (5 mm) of necrotic tissues from the spots were surface sterilized for 1 min in 0.5% NaOCl, washed twice with sterile distilled water, and plated onto peptone pentachloronitrobenzene agar. Plates were incubated at 28°C under 12-h light/dark for 7 days. The fungal colonies were purified using the hyphal-tip technique. A total of 152 fungal isolates were obtained, and the conidial morphology matched that of Curvularia and Bipolaris species, members of the Pleosporaceae family (Brecht et al. 2007; Garibaldi et al. 2014). Primers ITS1/ITS4 and GPDH-F/R were used to amplify and subsequently sequence the internal transcribed spacer (ITS1-5.8S-ITS2) region (White et al. 1990) and glycerol-3-phosphate dehydrogenase (gpd) gene, respectively. The gpd primer (GPDH-F, GTATCGTCTTCCGCAATG; GPDH-R, GAGGCGTTGGAGAGCAC) was designed using the genome of Curvularia victoriae FI3 that was obtained from the JGI website (https://genome.jgi.doe.gov/Cocvi1/Cocvi1.home.html). Bipolaris cactivora was successfully identified based on morphological characters and gene sequencing. Other species including B. sorghicola, B. papendorfii, B. sorokiniana, Curvularia aeria, C. affinis, C. eragrostidis, C. geniculata, C. hawaiiensis, and C. lunata were also successfully isolated and identified. In general, B. cactivora produced dark olive to black mycelia, floccose with black pigmentation on potato dextrose agar (PDA), and formed four to seven septate conidia, mostly straight and solitary with average size 56.9 × 13.4 µm. A phylogenetic tree was constructed using a neighbor-joining method, showing isolates B. cactivora A1022, K1282, K1283, and K1284 were grouped into the same clade of B. cactivora (ITS/gpd, HM598679/HM598682, Tarnowski et al. 2010). To examine virulence of B. cactivora, pathogenicity tests were performed three times by inoculating 5-week-old rice plants (variety MR211) with isolate B. cactivora K1283. Ten plants were inoculated by placing a conidial suspension (4 × 104 conidia/ml) from 8-day-old culture colonies, and 10 control plants were inoculated with distilled water. After 10 days, all inoculated leaves showed leaf spot at the inoculation points. Average length of necrosis formed by B. cactivora K1283 was 3.0 mm. B. cactivora K1283 was successfully reisolated from the necrotic tissues observed in symptomatic plants. No symptoms were observed in the control plants, and B. cactivora was not isolated from the controls. B. cactivora has been reported in Florida (U.S.A.) and Italy, where it occurs on bermudagrass and monstrose apple cactus, respectively (Brecht et al. 2007; Garibaldi et al. 2014). This study shows B. cactivora to be highly virulent on rice leaves, and to our knowledge this is the first report of B. cactivora causing leaf spot disease on rice.